Stem cells in the treatment of myocardial injury-induced cardiomyopathy: mechanisms and efficient utilization strategies - Yang, Jiali; Yue, Tian; He, Jian; Xiong, Shiqiang; Luo, Yan; Hou, Jun (Frontiers in Pharmacology, 2025)
Cardiac tissue injury and repair have always been a research hotspot in the field of cardiovascular disease. Limited and lost myocardial cells are non-renewable, and the current clinical treatment effect is still poor. The stem cells-based treatment strategy for cardiomyopathy is expected to solve the current treatment pain points. A variety of stem cells have the potential to differentiate into cardiomyocytes and form cardiac tissue, and the strong paracrine activity of stem cells also plays an important role in the regulation of inflammation, oxidative stress and cardiomyocyte apoptosis in cardiac tissue. Limited by the survival rate and stem cells activity after stem cells transplantation, the effect of stem cells therapy on cardiomyopathy is still not ideal. Pretreatment of stem cells or genetic modification to enhance the adaptability of stem cells to the environment, or the use of new biomaterials to assist stem cells transplantation is an effective optimization scheme and significantly enhances the therapeutic effect of stem cells therapy for cardiomyopathy. In this review, the types of stem cells widely studied in the treatment of cardiomyopathy, the role of stem cells in the treatment of cardiomyopathy, and how to efficiently use stem cells to treat cardiomyopathy are described in detail, which provides a theoretical basis for promoting the preclinical research and clinical transformation of stem cell therapy for cardiomyopathy.